Disposisi matematis dan peningkatan kemampuan berpikir kreatif siswa melalui pendekatan open-ended dengan setting kooperatif - Agung Cahya Gumilar (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2018)
The purpose of this study was to determine the increase in ability through each category of learning models, namely creative thinking and mathematical disposition, also the correlation between students’ mathematical creative thinking and mathematical dispositions. This study was conducted in the form of quasi-experimental with purposive sampling technique. The research applied Nonequivalent Control Group Design with sample subject of 65 students of Grade VIII at SMPN 3 Soreang. Hypothesis testing uses a mean similarity test with a significance level of 0, 05. Based on hypothesis testing, conclusions are obtained that: (1) the increase of creative thinking ability of students who get learning by Open Ended approach with Cooperative setting are better than students who get conventional learning; (2) there are different levels of increase in creative thinking skills of students who get learning by Open Ended approach with Cooperative setting and students who get conventional learning based on the initial mathematical ability categories (high, medium, and low); (3) the increase of mathematical disposition of students who get learning by Open Ended approach with Cooperative setting are better than the increase of mathematical disposition of students who get conventional learning; (4) there is a positive correlation between the ability of creative thinking and the content of educational learning using the Open Ended approaches with Cooperative settings.